A model for predicting anti littering behavioural intention among visitors of Kanching Recreation Forest in Malaysia - Talooki, Kambiz Yousefi (2019)
Littering is the most prevailing type of depreciative behaviour in Malaysian recreational forests. The litter prevalence can be attributed to the weakness of the managerial approaches in terms of covering all the determinant factors in the process of decision making which are necessary for a long term behavioural change among recreation users. Up to now a framework that can appropriately put all determinant psycho-social variables together and defined the linkage between them leading to stronger behavioural prediction has been lacking. Therefore, the current study attempted to propose a better prediction of Anti-littering Behavioural Intention (ALBI) at recreation forests through a combination of Theory of Planned Behaviour (TPB), Value Belief Norm Model (VBN), and an adaptation of Descriptive Norms (DN) and Anticipated Emotion (AE). This research was conducted at Kanching Recreation Forest (KRF) which is one of the Peninsular Malaysia’s recreation forests that has been suffering from the same issue. KRF was also chosen due to its proximity to two main cities including, Kuala Lumpur City and Rawang. Using time based stratified sampling, a total of 450 questionnaires were distributed among the KRF’s visitors, of which 419 were usable. The study’s results obtained from the Partial Least Square Structural Equation Modeling (PLS-SEM) showed a substantial improvement in total variance explained compared to both TPB and VBN. Visitors’ Injunctive Norm (IN) had the strongest positive relationship with their ALBI, followed by their Personal Norm (PN) and AE. The least relationship strength belonged to the Attitude of KRF’s visitors and their ALBI. Also, visitors’ Perceived Behavioural Control (PBC) had a positive small effect on their ALBI. On the other hand, the relationship between Ascription of Responsibility (AR) and DN of KRF’s visitors and their ALBI were not significant. Nevertheless, their DN showed a significant positive effect on their ALBI via the transmitting effect of their PN and AE. Their AR had an indirect effect on their ALBI via chain mediating effect of their PN and AE. The study results revealed an indirect relationship between IN of KRF’s visitors and their ALBI via transmitting effect of their PN and AE. Similarly, the effect of PBC on ALBI of KRF’s visitors was mediated via chain mediating effect of their AR, PN, and AE. The PN of KRF’s visitors had an indirect relationship with their ALBI via transmitting effect of AE. The findings of the study could potentially provide park managers and policymaker with ample material and information useful for the contents of their managerial intervention such as persuasive communication. It is hoped that via extraction of the most salient beliefs as a foundation of the factors that determine the recreation forest’s visitors behavioural intention, long-term anti-littering behavioural change can be achieved.